Pengaruh Pengadaan, Produksi, dan Distribusi Hijau Terhadap Kinerja Perusahaan pada Industri Kecil ban Menengah di Pekanbaru - Rahmawati, Riska; Berampu, Lailan Tawila; Daulay, Iwan Nauli (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
The manufacturing industry in Pekanbaru is showing growth along with increased productivity, reflecting improved performance in small and medium-sized industrial companies. The implementation of green supply chain management (GSCM) is one strategy believed to improve firm performance. This study aims to analyze the influence of three dimensions of GSCM—green procurement, green production, and green distribution—on firm performance. This study used a quantitative approach by distributing questionnaires to 45 small and medium-sized industrial companies in Pekanbaru. Data analysis was performed using SPSS software. The results of this study indicate that green production and green distribution have a significant effect on firm performance, while green procurement does not have a significant effect on firm performance.